Karakteristik Permen Gummy Temumangga (Curcuma mangga Val.) dengan Penambahan Sari Buah Nangka - Jeremia Mamanda Pelawi; Mohammad Prasanto Bimantio; Kusumastuti (Program Studi Teknologi Hasil Pertanian, 2023)
Gummy candy is a soft candy made with components such as gum, pectin, starch, carrageenan and gelatin. This research aims to determine the characteristics of gummy candy from the formulations of temumangga and jackfruit juice and using various concentrations of gelatin and determine the most preferred results for the gelatin concentration in making temumangga jelly candy with the addition of jackfruit juice. The experimental design used RBL (Complete Block Design) with 2 factors, factor I: concentration of temumangga extract and jackfruit juice (A1= 80 ml: 20 ml, A2= 60 ml: 40 ml, A3= 50 ml: 50 ml) and factors II gelatin concentration (B1= 5%, B2= 10%, B3= 15%). The parameters tested were physical texture analysis tests, gel strength, chemical tests for water content, ash content, coliform and organoleptic tests. The research results showed that the parameters of water content, ash content, reducing sugar and coliforms met SNI (No.3547-02-2008). The concentration of temumangga and jackfruit has a significant effect on water content, ash content, reducing sugar, coliforms, gel strength, texture hardness, texture cohesiveness, texture stickiness, organoleptics (color, taste, texture). Meanwhile, the concentration of gelatin has a significant effect on water content, ash content, reducing sugar, coliforms, texture hardness, gummy texture, texture cohesiveness, stickiness texture, organoleptics (aroma, texture,). The best gelatin concentration for color is 10% treated gelatin with a rating of 5.35 (Agak Suka). The best gelatin concentration for aroma is 15% treated gelatin with a rating of 5.00 (Agak Suka). The best gelatin concentration for taste is 15% treated gelatin with a rating of 5.33 (Agak Suka). The best gelatin concentration for texture is 15% treated gelatin with a rating of 4.85 (Netral).